2016
DOI: 10.1515/ohs-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

Growth rates of common pelagic ciliates in a highly eutrophic lake measured with a modified dilution method

Abstract: The growth rates of ciliates estimated under natural conditions with the widely used size fractionation method are much lower than those observed in cultures. However, recent studies performed with a modified dilution method demonstrated that the size fractionation method underestimates the ciliate growth, because it does not remove predators of the same size as the organisms studied. Thus, it is still unresolved whether ciliates are food-limited in different systems and whether their growth rates are indeed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Indeed, it had been previously observed that even slight change in salinity may cause pronounced changes in abundance of some pico-and nanoplanktonic protists in the Gulf of Gdańsk (Piwosz and Pernthaler, 2010). On the other hand, we did not investigate food webs factors, like grazing by meso-and microzooplankton, or bacterial food availability for bacterivorous hetero-and mixotrophic protists (Piwosz and Pernthaler, 2011;Rychert, 2016;Witek et al, 1997a), which likely are important considering elevated microbial activity in the Vistula River plumes (Ameryk et al, 2005;Wielgat-Rychert et al, 2013;Witek et al, 1997b). Further such ecological network studies would be important for explaining processes shaping protistan communities in estuaries, which are places of pivotal importance for understanding ecological and biogeochemical processes in coastal zones (Lunau et al, 2013;Schiewer and Schernewski, 2004).…”
Section: Patterns Of Pico-and Nanoplankton Protists Diversity In the mentioning
confidence: 94%
“…Indeed, it had been previously observed that even slight change in salinity may cause pronounced changes in abundance of some pico-and nanoplanktonic protists in the Gulf of Gdańsk (Piwosz and Pernthaler, 2010). On the other hand, we did not investigate food webs factors, like grazing by meso-and microzooplankton, or bacterial food availability for bacterivorous hetero-and mixotrophic protists (Piwosz and Pernthaler, 2011;Rychert, 2016;Witek et al, 1997a), which likely are important considering elevated microbial activity in the Vistula River plumes (Ameryk et al, 2005;Wielgat-Rychert et al, 2013;Witek et al, 1997b). Further such ecological network studies would be important for explaining processes shaping protistan communities in estuaries, which are places of pivotal importance for understanding ecological and biogeochemical processes in coastal zones (Lunau et al, 2013;Schiewer and Schernewski, 2004).…”
Section: Patterns Of Pico-and Nanoplankton Protists Diversity In the mentioning
confidence: 94%